A state‐of‐the‐art review on topologies and control techniques of solid‐state transformers for electric vehicle extreme fast charging. Issue 9 (15th May 2021) - Tahir, Yameena; Khan, Irfan; Rahman, Syed; Nadeem, Muhammad Faisal; Iqbal, Atif; Xu, Yinliang; Rafi, Mohammad
Abstract: Electrical vehicle (EV) technology has gained popularity due to its higher efficiency, less maintenance, and lower dependence on fossil fuels. However, a longer charging time is a significant barrier to its complete adaptation. Solid state transformer (SST) based extreme fast charging schemes have emerged as an appealing idea with an ability to provide a refuelling capability analogous to that of gasoline vehicles. Therefore, this paper reviews the EV charger requirements, specifications, and design criteria for high power applications. At first, the key barriers of using a traditional low frequency transformer (LFT) are discussed, and potential solutions are suggested by replacing the conventional LFT with high frequency SST at extreme fast‐charging (XFC) stations. Then, various SST‐based converter topologies and their control for EV fast‐charging stations are described. The reviewed control strategies are compared while considering several factors such as harmonics, voltage drop under varying loading conditions, dc offset load unbalances, overloads, and protection against system disturbances. Furthermore, the realization of SST for EV charging is comprehensively discussed, which facilitates understanding the current challenges, based on which potential solutions are also suggested.